Visa and Passport Expiry Reminder System - Mosbah, Abdulrahim (2009)
The University Utara Malaysia aspires to be a management university that is a paragon of efficiency and of world class level. In reaching this goal, UUM has opened its door to welcome a large number of international students, to the date this article is written, there are approximately 2000 international students in UUM. The large number of international students results in problem of the student visa renewal. It is not an easy task for the Unit of International Affairs to manage all the student visa renewal. Thus, this research proposes a development of a system that will remind students on the visa and passport expiry when the date is almost due. By sending SMS and emails, this system can reminder the international students to renew their visa. The development of this system is hoped to enhance the students' visa and passport management by the Unit of International Affairs of UUM.